2012
DOI: 10.1016/j.stem.2012.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Signaling Acts as a Neurogenic Switch by Repressing Sox2 in the Adult Neural Stem Cell Niche

Abstract: The subventricular zone (SVZ) neural stem cell niche contains mixed populations of stem cells, transit-amplifying cells, and migrating neuroblasts. Deciphering how endogenous signals, such as hormones, affect the balance between these cell types is essential for understanding the physiology of niche plasticity and homeostasis. We show that Thyroid Hormone (T(3)) and its receptor, TRα1, are directly involved in maintaining this balance. TRα1 is expressed in amplifying and migrating cells. In vivo gain- and loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
120
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(133 citation statements)
references
References 47 publications
(64 reference statements)
11
120
0
2
Order By: Relevance
“…As demonstrated by our group and others, the thyroid hormone is known to be a critical factor in promoting the neural differentiation of NSCs, both in the early stage of embryonic cortex and in the adult hippocampus [7,9,11]. These results suggested that the thyroid hormone probably acts in a different manner during different developmental stages.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…As demonstrated by our group and others, the thyroid hormone is known to be a critical factor in promoting the neural differentiation of NSCs, both in the early stage of embryonic cortex and in the adult hippocampus [7,9,11]. These results suggested that the thyroid hormone probably acts in a different manner during different developmental stages.…”
Section: Discussionsupporting
confidence: 61%
“…The effects of the thyroid hormone on NSCs in the adult hippocampus and the subventricular zone have also been well described [10,11]. However, the role of the thyroid hormone on NSC biology in the midbrain remains unclear.…”
mentioning
confidence: 99%
“…Perhaps the strongest evidence for H2B as the relevant USP22 substrate at the Sox2 locus comes from our observation that blocking H2B ubiquitylation by depleting ESCs of the H2B E3 ligase RNF20 results in decreased SOX2 expression. From a developmental standpoint, USP22-mediated repression of Sox2 may contribute to the embryonic lethality observed in USP22 null mice at day 9.5, a stage when Sox2 repression is critical for the differentiation of neural stem cells in the closing neuropore and developing brain (26,38,40,71,72).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, T 3 was demonstrated to exert critical roles in cell proliferation and NSC commitment toward neuroblasts in both the rodent SVZ and SGZ in vivo (15, 16). T 3 acts on transcription through nuclear receptors, Thyroid Hormone Receptors (TRs).…”
Section: Thyroid Hormone Regulates Adult Neurogenesismentioning
confidence: 99%
“…In vertebrates, different isoforms derive from the Thra (TRα2 and TRα2) and Thrb (TRβ1 and TRβ2) genes. The adult hippocampus expresses TRα1, TRβ1, and β2 isoforms (16, 34), whereas only TRα1 is expressed in the adult mouse SVZ (13, 15). …”
Section: Thyroid Hormone Regulates Adult Neurogenesismentioning
confidence: 99%